Analisis Implementasi Kebijakan Kawasan Tanpa Rokok di Wilayah Kerja Dinas Kesehatan Kabupaten Nagan Raya - Trianisya, Medinda; Darmawan, Darmawan; Paradhiba, Meutia; Duana, Maiza; Anwar, Sufyan (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2024)
The implementation of the no-smoking area policy within the Nagan Raya District Health Service is currently underway with posters prohibiting no-smoking areas affixed to the walls of every room in the Health Service office and also outside the room such as in the front yard and side yard of the office. Apart from posters, the message about the prohibition of smoking was also conveyed through banner media intended for all employees and visitors at the Nagan Raya Health Service. However, there are still many staff and visitors who smoke in these prohibited areas. The aim of the research is to see how the implementation, influencing factors and obstacles in the smoke-free area policy in Nagan Raya are implemented. The research method used is a qualitative method. Data was obtained from observations, interviews and submitted questionnaires by researchers directly to respondents at the Nagan Raya District Health Service. The results of the research show that the Nagan Raya Regency Government has established regional regulation number 3 of 2015 concerning smoking-free areas, implementation is carried out by spreading advice and outreach to the community. In its implementation, there are still obstacles, namely that there are still many staff who lack discipline by violating or not paying attention to these regulations. There are still visitors who don't know much about Non-Smoking Areas where there are restrictions on smoking areas and don't know the strict sanctions of these regulations. Suggestions to the government are expected to improve KTR regulations, the Health Service can be the spearhead in implementing KTR, the public is expected to be able to comply with government regulations regarding KTR policies.